Dinamika vnosa tujerodnih fitofagnih žuželk in pršic v Slovenijo - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2013)
An overview of alien phytophagous insects and mites that have been introduced or have spread into Slovenia since the mid-19th century is done. The most comprehensive list of these species ever published in Slovenia comprises 169 species, 164 insects and 5 mites. A chronological analysis of introduction and spreading dynamics as well as taxonomic affiliation and origin of these species is shown. Eighteen species, the occurrence of which has not been officially published yet in Slovenia, are briefly commented.
Keywords: alien insects; alien mites; plant pest; Slovenia; Slovenija; škodljivci rastlin; tujerodne pršice; tujerodne žuželke